Indirubin Treatment of Lipopolysaccharide-Induced Mastitis in a Mouse Model and Activity in Mouse Mammary Epithelial Cells - Jin-lun Lai; Yu-hui Liu; Yong-chong Peng; Pan Ge; Chen-fei He; Chang Liu; Ying-yu Chen; Ai-zhen Guo; Chang-min Hu (Hindawi Limited, 2017)
Indirubin is a Chinese medicine extracted from indigo and known to be effective for treating chronic myelogenous leukemia, neoplasia, and inflammatory disease. This study evaluated the in vivo anti-inflammatory activity of indirubin in a lipopolysaccharide- (LPS-) induced mouse mastitis model. The indirubin mechanism and targets were evaluated in vitro in mouse mammary epithelial cells. In the mouse model, indirubin significantly attenuated the severity of inflammatory lesions, edema, inflammatory hyperemia, milk stasis and local tissue necrosis, and neutrophil infiltration. Indirubin significantly decreased myeloperoxidase activity and downregulated the production of tumor necrosis factor-α, interleukin-1β (IL-1β), and IL-6 caused by LPS. In vitro, indirubin inhibited LPS-stimulated expression of proinflammatory cytokines in a dose-dependent manner. It also downregulated LPS-induced toll-like receptor 4 (TLR4) expression and inhibited phosphorylation of LPS-induced nuclear transcription factor-kappa B (NF-κB) P65 protein and inhibitor of kappa B. In addition to its effect on the NF-κB signaling pathway, indirubin suppressed the mitogen-activated protein kinase (MAPK) signaling by inhibiting phosphorylation of extracellular signal-regulated kinase (ERK), P38, and c-jun NH2-terminal kinase (JNK). Indirubin improved LPS-induced mouse mastitis by suppressing TLR4 and downstream NF-κB and MAPK pathway inflammatory signals and might be a potential treatment of mastitis and other inflammatory diseases.